METHODOLOGY OF TEACHING PHYSICAL EDUCATION IN UNIVERSITIES AT THE PRESENT STAGE (Scientific journal of the Fergana State University, 2024)
The article discusses the methodology of teaching physical education in universities at the present stage. Particular attention is paid to current approaches and techniques used by teachers to improve the effectiveness of student learning. The need to improve the methods of teaching physical education at universities is substantiated, and the reasons are given why approaches to the preparation of this discipline today are filled with new content. Modern legislation of the Republic of Uzbekistan meets the objectives of developing physical education and sports among young people, popularizing a healthy lifestyle, combining physical culture and general personal culture. However, the modern methodology of teaching the discipline “physical culture” has not only advantages, but also a number of disadvantages. Based on consideration of the advantages, disadvantages and analysis, it seems possible to adjust approaches to teaching this discipline in universities.